2022
DOI: 10.3390/polym14194215
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Simulation of MuCell®: The Effect of Key Processing Parameters on Cell Size and Weight Reduction

Abstract: Microcellular injection moulding is an important injection moulding technique to create foaming plastic parts. However, there are no consistent conclusions on the impact of processing parameters on the cell morphology of microcellular injection moulded parts. This paper investigates the influence of the main processing parameters, such as melt temperature, mould temperature, injection pressure, flow rate, shot volume and gas dosage amount, on the average cell size and weight reduction of a talc-reinforced poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Therefore, it can be concluded that in this case, the melt flow speed was significantly higher in the case of a smaller-thickness molding, which probably resulted in a reduction in the average size of the gas pores in the structure of these moldings. This is consistent with the effects described in papers [30,42,43]. For this reason, among others, the size of the pores in the 6 mm molding was lower than in the 8.4 mm moldings, which disturbed the linear relationship between the thickness of the molding and the size of the pores.…”
Section: X-ray Microtomography Analysissupporting
confidence: 91%
“…Therefore, it can be concluded that in this case, the melt flow speed was significantly higher in the case of a smaller-thickness molding, which probably resulted in a reduction in the average size of the gas pores in the structure of these moldings. This is consistent with the effects described in papers [30,42,43]. For this reason, among others, the size of the pores in the 6 mm molding was lower than in the 8.4 mm moldings, which disturbed the linear relationship between the thickness of the molding and the size of the pores.…”
Section: X-ray Microtomography Analysissupporting
confidence: 91%
“…Compared to POM gears, the micron‐sized cells formed in the microcellular injection molded PA66 gears were more abundant, as shown in Figure 4c. There was more gas dissolved into the polymer, 31 which accounted for the weight reduction difference between the foamed POM and foamed PA66. Moreover, most cells in PA66 gears had spherical shapes except for a proportion of ellipsoidal cells, which were deformed due to the flow of the melt during the filling process 26,32 .…”
Section: Resultsmentioning
confidence: 99%
“…Point 1 is located at the center of the sample just below the injection gate. Based on a previous simulation on the cell distribution [56], Points 2 to 5 are located in Z direction between the center and main area, and the distance between them and Point 1 is 33 mm. Since the temperature results in the horizontal direction of the sample cross-section exhibit little differences, Points 6 to 10 are selected near the sample side, and the distance between Point 6 and Point 1 is 75 mm.…”
Section: Part Design and Materialsmentioning
confidence: 99%